3D printing: Printing precision and application in food sector. (November 2017) - Liu, Zhenbin; Zhang, Min; Bhandari, Bhesh; Wang, Yuchuan
Abstract: Background: Three dimensional (3D) food printing is being widely investigated in food sector recent years due to its multiple advantages such as customized food designs, personalized nutrition, simplifying supply chain, and broadening of the available food material. Scope and approach: Currently, 3D printing is being applied in food areas such as military and space food, elderly food, sweets food. An accurate and precise printing is critical to a successful and smooth printing. In this paper, we collect and analyze the information on how to achieve a precise and accurate food printing, and review the application of 3D printing in several food areas, as well as give some proposals and provide a critical insight into the trends and challenges to 3D food printing. Key findings and conclusions: To realize an accurate and precise printing, three main aspects should be investigated considerably: material properties, process parameters, and post-processing methods. We emphasize that the factors below should be given special attention to achieve a successful printing: rheological properties, binding mechanisms, thermodynamic properties, pre-treatment and post-processing methods. In addition, there are three challenges on 3D food printing: 1) printing precision and accuracy 2) process productivity and 3) production of colorful, multi-flavor, multi-structure products. A broad application of this technique is expected once these challenges are addressed. Highlights: Factors affecting 3D food printing precision were discussed. Applications of 3D printing in food sector were reviewed. Challenges to 3D food printing were proposed.